Effect of sodium hydroxide on mechanical characteristics of kenaf fibers reinforced concrete - Baarimah, A. O.; Sharifah Maszura, Syed Mohsin; Alaloul, W. A.; Ba-naimoon, M. S. (IOP Publishing, 2021)
This article shows the experimental analysis of sodium hydroxide (NaOH) effects on the mechanical properties upon the addition of kenaf fibres to the concrete mixture. The compression and flexural tests were carried out on seven different concrete mixtures for 28 days to evaluate the mechanical characteristics. Hence, the experimental trials comprise of seven different mixtures of concrete; the control (without the addition of kenaf fibre) was represented as the first mixture. The following six concrete mixtures contain different kenaf fibre volume fractions (1% and 2%); they were treated with 1%, 3% and 6% of sodium hydroxide concentrations in order to investigate their performances. The experimental results show that the compressive and flexural strengths of kenaf fibres reinforced concrete increase as sodium hydroxide concentration increases. Besides, it is worth noting that the addition of kenaf fibres has an insignificant effect on the compressive strength of the concrete owing to the reduction in concrete density. Therefore, the results of this study demonstrated that the concrete flexural strength increased to up to 12%) upon the addition of 1% kenaf fibre associated with 6% NaOH. Moreover, the failure state increasingly changed to ductile from brittle.